2016
DOI: 10.1371/journal.pone.0165718
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Expression Profiling of Primary and Metastatic Renal Cell Carcinoma Stem Cell-Like Cancer Cells

Abstract: BackgroundRecent advancement in cancer research has shown that tumors are highly heterogeneous, and multiple phenotypically different cell populations are found in a single tumor. Cancer development and tumor growth are driven by specific types of cells—stem cell-like cancer cells (SCLCCs)—which are also responsible for metastatic spread and drug resistance. This research was designed to verify the presence of SCLCCs in renal cell cancer cell lines. Subsequently, we aimed to characterize phenotype and cell bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 102 publications
1
27
0
Order By: Relevance
“…In a metastatic RCC cell line, the expression of the OCT-4 and NANOG gene was significantly overexpressed compared to all other RCC cell lines (22). Our analysis also showed that higher levels of OCT-4 and NANOG expression were associated with worse survival of RCC patients, indicating these stem cell pluripotency factors might be a common pathway for inhibition of CSCs.…”
Section: Discussionsupporting
confidence: 55%
“…In a metastatic RCC cell line, the expression of the OCT-4 and NANOG gene was significantly overexpressed compared to all other RCC cell lines (22). Our analysis also showed that higher levels of OCT-4 and NANOG expression were associated with worse survival of RCC patients, indicating these stem cell pluripotency factors might be a common pathway for inhibition of CSCs.…”
Section: Discussionsupporting
confidence: 55%
“…High CD105 mRNA expression was previously associated with RCC metastases and high tumor stage 29 . In RCC cell lines CD105 www.nature.com/scientificreports www.nature.com/scientificreports/ was reported by us to be highly expressed in metastatic Caki-1 cell line before 12 , as well as by other groups 28 . Moreover, detection of CD105 marker in peripheral blood is considered to be effective tool to evaluate the early metastasis in RCC, especially in a cancer stem cell -positive conditions 30 .…”
Section: Discussionmentioning
confidence: 95%
“…Positive spheres were shown as green. present in most of RCC cell lines (SMKT-R3, Caki-2, 786-O, 769-P, RCC-6, Caki-1, ACHN and that CD105+ cells express also alkaline phosphatase (AP) 12 . The exact size of CD105+ cells subpopulation within the cell lines range from 0.03% (786-0), 0.06% (ACHN) to 2.17% (OS-RC2), but in as much as 90.93% (Caki-1) to 93.9% (SN12PM6) cells may be positive 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression profiles were also compared on kidney cancer samples and lung metastases using Affymetrix microarrays to identify genes that could potentially be targets of therapy [61]. Gene expression profiles were studied using microarrays on cultured metastatic RCC (ACHN) and primary RCC (CAKI-2) cell lines, to identify and analyze cancer stem cells [62]. In the works presented here, as well as in the works devoted to the analysis of the expression of individual genes [4,[9][10][11], missing information on the applicability of the revealed differences in expression as markers of metastasis.…”
Section: Discussionmentioning
confidence: 99%